Hybridization alters the gut microbial and metabolic profile concurrent with modifying intestinal functions in Tunchang pigs - He, Jiayi; Zhang, Yunchao; Li, Hui; Xie, Yanshe; Huang, Guiqing; Peng, Chen; Zhao, Pengju; Wang, Zhengguang (Frontiers in Microbiology, 2023)
Mammalian hybridization were widely used among Chinese wild boars for improving their growth performance and maintaining the meat quality. However, studies on the correlation between the hybridization and intestinal environment were still thin. In the current study, we confirmed that the hybrid Batun (BT, Berkshire×Tunchang) pigs had greater growth performance than the purebred Tunchang (TC) pigs. We also found that there was a microbial shift which included a higher ratio of Prevotella in BT pigs, indicating a shift to a faster-growing phenotype. But the untargeted metabolomic analyses revealed a more abundance of inflammation-related metabolites in BT pigs at growth stage, indicating an intestinal barrier defeat. The intestinal function analysis has showed a similar result that hybridization improved the nutrient metabolism and absorption, but decreased the intestinal barrier function. In addition, correlation analysis showed that these inflammation-related metabolites were associated with the different microbial communities, particularly Lactobacillus. The present study confirmed that the hybridization altered the intestinal microbiome, some of which overlap with effects on intestinal function. The findings highlighted the alteration of the intestinal microbiome and metabolome before and after the hybridization, as well as its impact on the host-microbiome interaction.